Clinical Pilot Study and Computational Modeling of Bitemporal Transcranial Direct Current Stimulation, and Safety of Repeated Courses of Treatment, in Major Depression. Issue 4 (December 2015) - Ho, Kerrie-Anne; Bai, Siwei; Martin, Donel; Alonzo, Angelo; Dokos, Socrates; Loo, Colleen K.
Abstract : Objectives: This study aimed to examine a bitemporal (BT) transcranial direct current stimulation (tDCS) electrode montage for the treatment of depression through a clinical pilot study and computational modeling. The safety of repeated courses of stimulation was also examined. Methods: Four participants with depression who had previously received multiple courses of tDCS received a 4-week course of BT tDCS. Mood and neuropsychological function were assessed. The results were compared with previous courses of tDCS given to the same participants using different electrode montages. Computational modeling examined the electric field maps produced by the different montages. Results: Three participants showed clinical improvement with BT tDCS (mean [SD] improvement, 49.6% [33.7%]). There were no adverse neuropsychological effects. Computational modeling showed that the BT montage activates the anterior cingulate cortices and brainstem, which are deep brain regions that are important for depression. However, a fronto-extracephalic montage stimulated these areas more effectively. No adverse effects were found in participants receiving up to 6 courses of tDCS. Conclusions: Bitemporal tDCS was safe and led to clinically meaningful efficacy in 3 of 4 participants. However, computational modeling suggests that the BT montage may not activate key brain regions in depression more effectively than another novel montage—fronto-extracephalic tDCS. There is also preliminary evidence to support the safety of up to 6 repeated courses of tDCS.